COLLABORATION BETWEEN BUMDES AND MSMES IN ACCELERATING HALAL CERTIFICATION FOR FOOD AND BEVERAGE PRODUCTS IN MADURA - Fajar, Fajar; Adiyono, Adiyono (Universitas Al-Amien Prenduan, 2024)
AbstractThe implementation of the halal certification program in Indonesia, especially in Bangkalan Regency, has not yet run optimally. This can be proven by the large number of SMEs who do not yet have halal certification. This research has several objectives, including (1) To find out the mechanism for managing MSME products in Bangkalan. (2) To describe the application of halal certification to MSME products in Bangkalan. (3) To find out and analyze the role of BUMDes in providing services to the community, especially MSMEs in Bangkalan. (4) To identify optimization of BUMDes services in Bangkalan. This research is descriptive analytical in nature using a juridical-empirical approach. This approach is used because of the characteristics of the law itself. The data collection technique for this research is a survey which takes samples from a population and uses interviews as a data collection tool in addition to literature study. The results of this research show that first, there are only a few MSMEs that already have legal or household product permits. Second, the majority of MSMEs in Bangkalan do not yet have halal certification, this is due to their ignorance about the existence of halal certification. Third, the role of BUMDes in the halal certification issue is still not optimal. This is because most village-owned enterprises still focus on managing tourism and service units.